Rancang Bangun Alat Penetralisir Asap Rokok pada Ruang Tamu Berbasis Internet of Things - Dika, Andika Zahrah Ramadhanti; Luki Hernando; Joni Eka Candra (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2024)
Cigarette smoke is one type of air pollutant that can cause various health problems, such as coughing, cancer and other health problems, especially when accumulated in the house, especially in the living room which is often used for gathering. This research aims to design and build an Internet of Things (IoT)-based cigarette smoke neutralization device that utilizes MQ-2 and MQ-135 sensors to detect the presence of smoke and harmful substances. The method used in this research is the waterfall method, which includes requirements analysis, design, implementation, testing, and maintenance. The development process of this tool is carried out systematically. This tool is equipped with a bot telegram notification system that provides real-time information to users regarding the air quality in the living room. When the sensor detects pollution levels exceeding the threshold, the device will activate the fan to increase air circulation and utilize the exhaust fan to neutralize smoke. In addition, the sound output from the speaker provides information about the air quality and notifies that the room has been successfully neutralized. Based on the test results, this prototype tool is able to detect air quality and takes ±1 minute to neutralize a room contaminated with smoke > 10 ppm while for smoke levels > 50 ppm, it takes ±2 minutes to create a healthy environment for the occupants. This research is expected to provide an innovative solution to the problem of smoke pollution and the implementation of indoor smoking bans.